2019
DOI: 10.1051/epjconf/201920302005
|View full text |Cite
|
Sign up to set email alerts
|

Side emissions during EC injection for PDI studies in FTU tokamak

Abstract: The evidence of Parametric Decay Instabilities (PDI) excited by the ECH power injected in O-Mode has been explored in FTU Tokamak, using the Collective Thomson Scattering (CTS) diagnostic. The experiments show evidences to support the hypothesis of low-threshold excitation of waves generated by PDI mechanisms, formerly proposed in the case of 2nd harmonic X-mode injection in TEXTOR and ASDEX-U. Theoretical analysis predicts low-threshold parametric decay also for O-mode pump-wave injection, which can be inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Second, theoretical predictions of strong PDI-related microwave signals near 1.5 times the ECRH frequency [29] should be investigated experimentally and their potential consequences for ITER assessed. Third, it would be of interest to carry out investigations similar to the ones found in the present paper for PDIs involving an O-mode pump wave decaying to a single trapped UH wave and a low-frequency daughter wave near the UHR when the UHR occurs near a local maximum of the electron density [62][63][64][65][66][67][68][69]. Such PDIs are predicted to occur in connection with MHD modes for 170 GHz fundamental O-mode ECRH of the full field (on-axis toroidal magnetic field strength of 5.3 T) scenarios and 104 GHz (or 110 GHz) fundamental O-mode ECRH of half field scenarios at ITER [62][63][64].…”
Section: Data Availability Statementmentioning
confidence: 83%
“…Second, theoretical predictions of strong PDI-related microwave signals near 1.5 times the ECRH frequency [29] should be investigated experimentally and their potential consequences for ITER assessed. Third, it would be of interest to carry out investigations similar to the ones found in the present paper for PDIs involving an O-mode pump wave decaying to a single trapped UH wave and a low-frequency daughter wave near the UHR when the UHR occurs near a local maximum of the electron density [62][63][64][65][66][67][68][69]. Such PDIs are predicted to occur in connection with MHD modes for 170 GHz fundamental O-mode ECRH of the full field (on-axis toroidal magnetic field strength of 5.3 T) scenarios and 104 GHz (or 110 GHz) fundamental O-mode ECRH of half field scenarios at ITER [62][63][64].…”
Section: Data Availability Statementmentioning
confidence: 83%
“…A frequency between 700 and 900 MHz is expected at the point on the UH layer reached by the reflected X wave. Compatible anomalous signals, collected by the receiving system of the CTS diagnostic for that discharge, are shown in figure 5b (more details about of the anomalous emissions of CTS experiments at FTU are reported in [27]). This is an example of the features offered by the CTS data analysis code, which will be exploited for the detailed analysis of the data collected during all the discharges of the past experimental campaigns.…”
Section: Integration Of the Multi-reflection Gray Codementioning
confidence: 99%
“…Apart from the PDIs driven by X-mode ECRH, PDIs driven by O-mode ECRH, relevant for the full-field ITER scenarios [12], have also been investigated. Particularly, decay of an O-mode ECRH wave to a trapped UH wave and a low-frequency lower hybrid wave has been investigated theoretically [53][54][55][56], in a lowtemperature plasma filament [3], and at the FTU tokamak [57][58][59]. Additionally, it has recently been suggested that trapped low-frequency waves existing as a consequence of the strong gradients in the ITER and ASDEX Upgrade pedestals could lead to PDIs near the plasma edge during O-mode ECRH [60].…”
Section: Introductionmentioning
confidence: 99%